Next-generation sequencing analysis identifies genomic alterations in pathological morphologies: A case of pulmonary carcinosarcoma harboring EGFR mutations. (August 2018) - Koba, Hayato; Kimura, Hideharu; Nishikawa, Shingo; Sone, Takashi; Abo, Miki; Hara, Johsuke; Hosomichi, Kazuyoshi; Tajima, Atsushi; Kasahara, Kazuo
Highlights: A case with lung carcinosarcoma with two components, an adenocarcinoma component and a chondrosaroma component. Both histological components carried deletional mutations in exon 19 of EGFR . Next-generation sequences found five identical alterations shared by the two components. Abstract: Objectives: Pulmonary carcinosarcoma is a rare lung malignancy and little analysis has been performed to identify associated genomic alterations. We used next-generation sequencing (NGS) to analyze a pulmonary carcinosarcoma harboring an epidermal growth factor receptor (EGFR) mutation. Materials and methods: The lung carcinosarcoma used for this study contained components of adenocarcinoma and chondrosarcoma and originated from a 73-year-old female. Both components carried deletion mutations in exon 19 of EGFR and both had equally strong EGFR protein expression. This study analyzed the biological and genetic characteristics of both components, using NGS and immunohistochemical (IHC) staining. Results and conclusion: IHC staining revealed that both total EGFR and deletion mutation specific EGFR proteins were equally expressed in both components. Intriguingly, identification of genomic alterations with NGS found five identical alterations in four genes ( EGFR, CBLB, TP53, and MEN1 ) that were shared by the two components, and that each component had a large number of individual alterations. Additionally, we focused on an alpha-thalassemia/mental retardation syndrome X-linked (ATRX) mutation which was only present in the sarcoma component. ATRX protein expression was also only detected in the sarcoma component. This is the first report of the exhaustive genomic alterations in a pulmonary carcinosarcoma harboring an EGFR mutation. The results show that our case had the same EGFR status in both components. The EGFR mutation is the driver mutation in both components. In our case, we found that TP53 may be a common alteration and ATRX may be a specific alteration in the sarcoma component.